Terra nullius - J. Mallard (Law Text Culture, 1998)
Tonight the stars shine so bright against their backdrop of infinity. I arrived here in Sharks Bay this morning at 9.00 am after hiring a lift from the roadhouse with the town taxi driver who knew of Joe Mallard when he was young,...and had lots to say about Mabo and the World Heritage issue ... - Journal excerpt Sat Aug 7 1993